Myocardial performance during progressive exercise in athletic adolescent males - Rowland, T. W.; Garrard, M.; Marwood, S.; Guerra, M. E.; Roche, D.; Unnithan, V. B. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The extent that enhanced ventricular function contributes to superior aerobic fitness of trained athletes is unclear. This study compared cardiovascular responses to progressive cycle exercise in 12 adolescent soccer players and 10 untrained boys with assessment of ventricular inotropic and relaxation properties by Doppler ultrasound techniques.